Speed Control of DC Motor Using Chopper Based on Fuzzy Logic. (August 2019) - Singh, Arunesh kumar; Saxena, Abhinav; Poon Terang, Parveen; Tulsyan, Palak; Waris, M
Abstract: This paper present the speed control of DC Motor based on boost converter under the controlling of fuzzy logic. The DC motor has armature and field winding in which armature winding is controlled by using boost converter which is triggered by fuzzy logic controller which consist of 7x7 rule and the input are change in error and rate of change of error and output is firing angle. The fuzzy logic controller gives smooth, reliable, efficient speed controlling of DC motor. Further the compative analysis between fuzzy logy and PID controller is assessed. The complete system is designed with SIMULINK/MATLAB for perfect analysis between two methods mentioned.